Pengaruh Manajemen Pengetahuan terhadap Kinerja Bisnis UMKM di Indonesia: Peran Mediasi Inovasi Hijau dan Pengambilan Keputusan - Carissa, Manda; Yuwono, Wisnu; Anggraini, Ratih (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The study aims to analyze the influence of knowledge management on the business performance of micro, small, and medium enterprises (MSMEs) in Indonesia, with green innovation and decision-making as mediating variables. Using a quantitative approach and PLS-SEM method on 300 MSMEs, the analysis results reveal that knowledge management has no significant direct effect on business performance, but has a significant positive effect on green innovation and decision-making. Furthermore, decision-making is found to have a strong positive effect on business performance, while green innovation shows a negative effect on business performance. These findings highlight the central role of decision-making as a key mediator in the relationship between knowledge management and business performance. This study offers practical insights for strengthening knowledge management and decision-making strategies in the context of developing resilient and sustainable MSMEs.